PEMIKIRAN EKONOMI ISLAM; KILASAN TOKOH DAN PEMIKIRANNYA - Ahmad Wahyudi Zein; Muhammad Dimas Arif; Asyhari abdillah siregar; Sandi sipahutar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to examine and analyze Islamic economic thinking from leading figures in history, such as Ibn Khaldun, Al-Ghazali, and Yusuf al-Qaradawi, identifying the contribution of their thinking to Islamic economic theory and practice that is relevant to Indonesia's social and economic conditions. , Develop a model or framework of Islamic economic thought that can be applied in overcoming contemporary economic problems, such as social inequality and unfair distribution of wealth. This research uses a qualitative approach with data collection techniques through library research, which aims to explore and analyze Islamic economic thought from leading figures such as Ibn Khaldun, Al-Ghazali, and Yusuf al-Qaradawi, as well as its relevance to contemporary economic challenges. Data will be collected through library sources which include books, scientific articles and journals that discuss classical and modern Islamic economic concepts. In conclusion, Islamic economic thought developed by figures such as Ibn Khaldun, Al-Ghazali, and Yusuf al-Qaradawi provides a very relevant and applicable foundation in overcoming contemporary economic challenges, such as social inequality, poverty, unemployment, and wealth distribution. These thoughts emphasize the importance of social justice, prohibition of usury, redistribution of wealth through zakat, and wise and sustainable management of resources.